Optimalisasi Zakat Fitrah dalam Meningkatkan Kesejahteraan Ekonomi Umat di Desa Ujung Tanah Kecamatan Bola - Fadilah, Ika Nur; Isyana, Ina; Hasbi, Hartas (Universitas Serambi Mekkah, 2024)
The majority of Indonesians embrace Islam by having the obligation to pay zakat. Zakat represents the potential and foundation of Islamic economy. An ideal zakat policy will have the potential to improve the quality of life of the general public. Every Muslim is required to pay zakat fitrah during the month of Ramadan or before Eid al-Fitr. The system of distributing and receiving zakat fitrah can be done by using cash or rice as food. In several areas, one of which is in Ujung Tanah village, zakat fitrah is usually given in the form of rice. Zakat fitrah is usually carried out on the 23rd day of Ramadan in Ujung Tanah village. This research aims to understand the distribution of zakat fitrah in Ujung Tanah in relation to poverty alleviation. This research will describe how the mechanism of zakat fitrah management in Ujung Tanah village and the extent to which the collected zakat fitrah has an impact on improving the economic welfare of the people in Ujung Tanah village. The findings of the study show that the system of collecting and distributing zakat fitrah in Ujung Tanah is carried out by silent visits by the community to the residence of the Village Imam. The community handed over to the zakat officer, namely the village imam himself, then a record was made to find out the number of souls and zakat from each zakat given by the community.